Federal government support for agriculture in Nigeria: Analysis with a public expenditure lens - Nwoko, Chinedum; Ikejiofor, Amarachi Grace; Nnaji, Nchedo Theresa; Mogues, Tewodaj (International Food Policy Research Institute, 2018)
This paper provides a broad view of public sector support to agriculture in Nigeria, through the lens of the allocation of public expenditures by the federal government in support of the sector. We consider the adequacy and stability of agricultural public spending during the period of 2007 to 2016, drawing on data from the Ministry of Finance, the Office of the Accountant General of the Federation, and other sources.